2015
DOI: 10.1007/s11357-015-9767-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of apoptosis in slow and fast twitch muscles of aged female F344BN rats

Abstract: Age-related muscle atrophy is characterized by decreases in muscle mass and is thought be mediated, at least in part, by increases in myocyte apoptosis. Recent data has demonstrated that the degree of muscle loss with aging may differ between males and females while other work has suggested that apoptosis as indicated by DNA fragmentation may be regulated differently in fastand slow-twitch muscles. Herein, we investigate how aging affects the regulation of muscle apoptosis in the fast-twitch extensor digitorum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(54 reference statements)
2
2
0
Order By: Relevance
“…Given that lifelong elevations of HSP in skeletal muscle provides protection against damage and facilitates successful recovery after damage in muscles of old mice [22], the findings in the present study strongly suggest that the upregulation of HSPs might mediate the protective effects of G1 in skeletal muscles after estrogen loss. This concept is also supported by the favorable changes of mitochondrial and apoptosis-related gene expression after G1 treatment in OVX rats, which is consistent with previous findings showing that HSPs improve mitochondrial function [19], and protect cells against apoptosis [23]. Apoptosis of skeletal muscle fibers and satellite cells is considered a possible contributor to aging decrements that occur in skeletal muscle [23,24].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Given that lifelong elevations of HSP in skeletal muscle provides protection against damage and facilitates successful recovery after damage in muscles of old mice [22], the findings in the present study strongly suggest that the upregulation of HSPs might mediate the protective effects of G1 in skeletal muscles after estrogen loss. This concept is also supported by the favorable changes of mitochondrial and apoptosis-related gene expression after G1 treatment in OVX rats, which is consistent with previous findings showing that HSPs improve mitochondrial function [19], and protect cells against apoptosis [23]. Apoptosis of skeletal muscle fibers and satellite cells is considered a possible contributor to aging decrements that occur in skeletal muscle [23,24].…”
Section: Discussionsupporting
confidence: 86%
“…This concept is also supported by the favorable changes of mitochondrial and apoptosis-related gene expression after G1 treatment in OVX rats, which is consistent with previous findings showing that HSPs improve mitochondrial function [19], and protect cells against apoptosis [23]. Apoptosis of skeletal muscle fibers and satellite cells is considered a possible contributor to aging decrements that occur in skeletal muscle [23,24]. …”
Section: Discussionsupporting
confidence: 86%
“…In fast-twitch muscle, our results showed that the apoptotic pathway was significantly enriched in the old group compared to the young group ( Figure 6A and Table 8 ), whereas no significant difference was observed with aging in terms of myogenesis. Considering that the muscle mass-to-body weight ratio is decreased in fast-twitch muscle with age [ 50 ], the cause of atrophy may be largely owing to changes in the apoptotic process due to aging, not myogenesis. Unlike GAS, no significant difference in the apoptotic process due to aging was seen in SOL, while myogenesis was significantly enriched in the young group compared to the old group ( Figure 7A ).…”
Section: Discussionmentioning
confidence: 99%
“…According to prior study, age-related muscle atrophy mainly relies on intrinsic apoptotic pathway and this process are different between slow and fast-twitch muscle [ 51 , 53 56 ]. In detail, caspase-9, which is a key molecule in the intrinsic apoptotic pathway, were significantly up-regulated in fast-twitch muscle by aging, whereas were not in slow-twitch muscle [ 50 ]. Since it has been not determined whether chronic exercise results in down-regulation of apoptosis by modulating the amount and activity of caspase-9 in fast-twitch muscle, further study need to be performed.…”
Section: Discussionmentioning
confidence: 99%